Application of a Lumped Parameter Model to Study the Feasibility of Simultaneous Implantation of a Continuous Flow Ventricular Assist Device (VAD) and a Pulsatile Flow VAD in BIVAD Patients. Issue 3 (March 2017) - Di Molfetta, Arianna; Ferrari, Gianfranco; Iacobelli, Roberta; Filippelli, Sergio; Fresiello, Libera; Guccione, Paolo; Toscano, Alessandra; Amodeo, Antonio
Abstract: The aim of this work is to develop and test a lumped parameter model of the cardiovascular system to simulate the simultaneous use of pulsatile (P) and continuous flow (C) ventricular assist devices (VADs) on the same patient. Echocardiographic and hemodynamic data of five pediatric patients undergoing VAD implantation were retrospectively collected and used to simulate the patients' baseline condition with the numerical model. Once the baseline hemodynamic was reproduced for each patient, the following assistance modalities were simulated: (a) CVAD assisting the right ventricle and PVAD assisting the left ventricle (RCF + LPF), (b) CVAD assisting the left ventricle and PVAD assisting the right ventricle (LCF + RPF). The numerical model can well reproduce patients' baseline. The cardiac output increases in both assisted configurations (RCF + LPF: +17%, LCF + RPF: +21%, P  = ns), left (right) ventricular volumes decrease more evidently in the configuration LCF + RPF (RCF + LPF), left (right) atrial pressure decreases in the LCF + RPF (RCF + LPF) modality. The pulmonary arterial pressure slightly decreases in the configuration LCF + RPF and it increases with RCF + LPF. Left and right ventricular external work increases in both configurations probably because of the total cardiac output increment. However, left and right artero‐ventricular coupling improves especially in the LCF + RPF (−36% for the left ventricle and −21% for the right ventricle, P  = ns). The pulsatility index decreases by 8.5% in the configuration LCF + RPF and increases by 6.4% with RCF + LPF ( P  = 0.0001). A numerical model could be useful to tailor on patients the choice of the VAD that could be implanted to improve the hemodynamic benefits. Moreover, a model could permit to simulate extreme physiological conditions and innovative configurations, as the implantation of both CVAD and PVAD on the same patient.